Case Report: When cystic fibrosis, elexacaftor/tezacaftor/ivacaftor therapy, and alpha1 antitrypsin deficiency get together - Kinuani, Rachel; Ezri, Jessica; Kernen, Yann; Rochat, Isabelle; Blanchon, Sylvain (Frontiers in Pediatrics, 2024)
In the last 10 years, the care of patients with cystic fibrosis (CF) have been revolutionized with the introduction of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) modulator drugs, with major impact on symptoms and life expectancy, especially considering the newest and highly effective ELEXACAFTOR/TEZACAFTOR/IVACAFTOR (ELX/TEZ/IVA). On the other hand, adverse effects are relatively frequent, and life-threatening ones have been reported including severe hepatitis. In children starting CFTR modulators, clinical trials reported 10-20% of patients with increasing transaminases >3xULN when real-life studies reported a discontinuation rate three times higher than phase 3 studies. We report the case of a 10-year boy with CF developing severe acute hepatitis 2 weeks after starting ELZ/TEZ/IVA. The exhaustive screening of potential causes led to the identification of heterozygous alpha1-antitrypsine (AAT) deficiency with genotype MZ. The Z allele of SERPINA1 gene, encoding AAT, is known as risk factor for CF liver disease. We hypothesized that it may act as a risk factor for drug-induced liver injury of CFTR modulator, notably ELZ/TEZ/IVA. Therefore, checking AAT before starting CFTR modulator can be suggested, in particular for children with previous, even transient, liver disease